Renal manifestations in adults with mitochondrial disease from the mtDNA m.3243A>G pathogenic variant - Clara Gonçalves Bacelar (2021)
Mitochondrial diseases are a clinically and genetically heterogeneous group of disorders, that typically have a multisystemic involvement. The m.3243A>G pathogenic variant is the most frequent mitochondrial DNA defect, and it causes several different clinical syndromes, such as the mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS), and the maternally inherited diabetes and deafness (MIDD) syndromes. Not frequently reported, renal involvement in these diseases is probably underestimated, yet it represents an important aggravating factor in the morbidity of these patients. It generally manifests as subnephrotic proteinuria and progressive deterioration of kidney function. Adult presentation of mitochondrial diseases is hard to recognize, especially in oligosymptomatic patients or those with exclusive kidney involvement. However, suspicion should always arise when family history, particularly on the maternal side, and multisystemic symptoms, most often of the central nervous system and skeletal muscles, are present. Current treatment options for mitochondrial cytopathies are largely supportive. Genetic counselling is important in mitochondrial disorders, to provide patients with accurate information about prognosis, recurrence risk, and reproductive choices.